(untitled) (Research, Society and Development, 2021)
The Utinga State Park (PEUt) is one of the few green areas with the function of preserving the biodiversity remaining in the urbanization process of the Belém area. Add to this the fact that the effectiveness of the use control is directly linked to maintaining the quality of the city’s water supply. In this context, the idea of environmental protection involves different perspectives, which are directly linked to territorial challenges in view of the patterns of development of the metropolitan form in the Amazon.